A Centrosymmetric Organic Semiconductor with Donor–Acceptor Interaction for Highly Photostable Organic Transistors. (10th February 2022) - Zhang, Haoquan; Hu, Yongxu; Chen, Xiaosong; Yu, Li; Huang, Yinan; Wang, Zhongwu; Wang, Shuguang; Lou, Yunpeng; Ma, Xiaonan; Sun, Yajing; Li, Jie; Ji, Deyang; et al.
Abstract: Molecule design of organic semiconductors (OSCs) for eliminating photoresponse and maintaining high charge mobility concurrently is beneficial to realize intrinsically photostable and high‐performance organic field‐effect transistors (OFETs), which has never been reported. Here, a novel organic semiconductor TFP‐TT‐TPA with a centrosymmetric structure is synthesized. Remarkably, OFETs with TFP‐TT‐TPA show negligible photoresponse under light intensity up to 170.4 mW cm −2 (higher than sunlight intensity, about 138 mW cm −2 ), which ensures that the devices can work stably under sunlight. Through the single‐crystal structure and exciton dynamics analysis, it is found that the specific structure design can make strong intermolecular D–A interaction that occurs in the aggregate state, which facilitates the process of exciton quenching and thus enables the photostable OFETs. This study provides a new strategy for the design of organic semiconductors with intrinsic photostability and the construction of photostable organic optoelectronic devices for applications in light environment. Abstract : Suppressing the photo‐response of organic semiconductors is realized in a novel centrosymmetric molecule (TFP‐TT‐TPA) with donor‐acceptor groups, which originates from the exciton quenching effect induced by strong intermolecular interaction. Remarkably, organic transistors based on TFP‐TT‐TPA show excellent photostability under high light irradiation intensity of 170.4 mW cm −2, which is higher than sunlight intensity. This study indicates the potential application under sunlight.